Antiobesity drugs utilization trend analysis and reimbursement lists status – the perspective of selected European countries - Stević, Ivana; Vajagić, Maja; Knežević, Bojana; Raičević, Branislava; Janković, Slobodan; Krajnović, Dušanka; Milošević Georgiev, Andrijana; Lakić, Dragana; Odalović, Marina (Archives of Pharmacy, 2024)
Obesity is a chronic, complex, relapsing disease impacting healthcare systems and the economy worldwide. We aim to analyze the utilization trends of antiobesity drugs, and their reimbursement status on drug lists of health insurance funds (HIF) in selected European countries. The DDD/1000 inhabitants/day methodology is used for utilization trend analysis, where data from official national utilization reports were used. For the reimbursement status analysis of 5 antiobesity drugs (orlistat, semaglutide, liraglutide, naltrexone/bupropion, setmelanotide), the websites of national health insurance funds (HIF) of 22 European countries were screened. Trend analysis revealed fluctuation for almost all antiobesity drugs (the highest decrease seen for orlistat in Serbia, and the highest increase for liraglutide in Croatia). Novel antiobesity drugs show an increasing utilization trend in almost all the countries. In two out of three European countries, antiobesity drugs are not covered by the HIF. Slovenia and Denmark reimburse most of the antiobesity drugs. The Netherlands is the only country where the cost of setmelanotide is paid by the HIF. Our results emphasize the importance of prioritizing the introduction and implementation of new strategies and reimbursement scheme models in global and national antiobesity policies.